Identifying a motor proficiency barrier for meeting physical activity guidelines in children. Issue 1 (January 2018) - De Meester, An; Stodden, David; Goodway, Jacqueline; True, Larissa; Brian, Ali; Ferkel, Rick; Haerens, Leen
Abstract: Objectives: This study examined the existence of a threshold level (proficiency barrier) of actual motor competence (MC) below which a child is not likely to attain 60 min of moderate-to-vigorous physical activity (MVPA) per day. Design: A cross-sectional study. Methods: Actual MC was assessed in 326 children (48.5% boys; age = 9.50 ± 1.24 years) using the Test of Gross Motor Development-2; MVPA was measured with ActiGraph GT3X + accelerometers. Perceived MC, included as a potential mediating variable, was assessed with the Self-Perception Profile for Children. Binary logistic (mediation) regression analyses controlling for sex and a chi-squared test were used to gain insight into the relationship between (the levels of) actual MC and the percentage of children meeting the MVPA guideline. Results: Actual MC significantly predicted the percentage of children meeting the guideline (B = .03, SE  = .01, p <  .001), even when controlling for sex. Perceived MC did not mediate this relationship. Children with high actual MC (65–100 percentile) were 2.46 ( p  = .003) times more likely to meet the guideline than children with low actual MC (0–27 percentile). Conclusions: The present study demonstrates the potential impact of low MC on children's MVPA levels and suggests evidence for the existence of a proficiency barrier for meeting MVPA guidelines. Almost 90% of the children whose actual MC is below the 'average' threshold do not meet the MVPA guideline. As more children with higher levels of actual MC meet the guideline than their less competent peers, it is crucial to provide opportunities to sufficiently develop children's actual MC.